A multicenter study on the quantification of liver iron concentration in thalassemia patients by means of the MRI T2* technique - Xu, Fengming; Peng, Yuzhao; Xie, Hanhong; Liang, Bumin; Yang, Gaohui; Zhao, Fanyu; Liu, Yu; Peng, Peng (Frontiers in Medicine, 2023)
Objective To investigate the feasibility and accuracy of quantifying liver iron concentration (LIC) in patients with thalassemia (TM) by 1.5T and 3T T2* MRI. Methods 1.5T MRI T2* values were measured in 391 TM patients from three medical centers: The T2* values of the test group were combined with LIC (LICF) provided by FerriScan to construct the curve equation. In addition, the liver 3T MRI T2* data of 55 TM patients were measured as the 3T group: the curve equation of 3T T2* value and LICF was constructed. Results Based on the test group LICF (0.6-43 mg/g dw) and the corresponding 1.5T T2* value, the equation was LICF=37.393T2*^(-1.22) (R2=0.971, P<0.001). There was no significant difference between LICe-1.5T and LICF in each validation group (Z=-1.269, -0.977, -1.197, P=0.204, 0.328, 0.231). There were significant consistency (Kendall's W=0.991, 0.985, 0.980, all P<0.001) and high correlation (rs=0.983, 0.971, 0.960, all P<0.001) between the two methods. There was no significant difference between the clinical grading results of LICe-1.5T and LICF in each validation group (2=3.0, 4.0, 2.0, P=0.083, 0.135, 0.157), and there was significant consistency between the clinical grading results (Kappa's K=0.943, 0.891, 0.953, P<0.001). There was no statistical correlation between the LICF (≥14mg/g dw) and the 3T T2* value of severe iron overload (P=0.085). The LICF (2-14 mg/g dw) with mild and moderate iron overload was significantly correlated with the corresponding T2* value (rs=-0.940, P<0.001). The curve equation constructed by LICF and corresponding 3T T2* values in this range is LICF=18.463T2*^(-1.142) (R2=0.889, P<0.001). There was no significant difference between LICF and LICe-3T in the mild to moderate range (Z=-0.523, P=0.601), and there was significant correlation (rs=0.940, P<0.001) and significant consistency (Kendall's W=0.970, P=0.008) between them. LICe-3T had high diagnostic efficiency in the diagnosis of severe, moderate and mild liver iron overload (specificity=1.000, 0.909, sensitivity =0.972, 1.000). Conclusion LIC can be accurately quantified based on the 1.5T T2* value of liver and the specific LIC-T2* curve equation. 3T T2* technology can accurately quantify mild to moderate LIC, but it isn’t recommended to use 3T T2* technology to quantify higher iron concentrations.